Social Company Disrupts Fear Memory Renewal: Evidence From Two Rodent Studies - Yuan, Jiajin; Yan, Minmin; Xu, Yin; Chen, Weihai; Wang, Xiaqing (Frontiers in Neuroscience, 2018)
Renewal of fear when leaving treatment context is a challenge for behavioral therapies. Prior studies suggest a social buffering effect that fear response may be attenuated in the presence of social company. However, few studies have examined the role of social buffering in reducing fear renewal. Here we used a Pavlovian fear conditioning procedure involving ACC and ABC models (the capital letter denotes acquisition, extinction, and test, respectively) to examine the effect of social buffering on fear memory renewal in male rats. All conditioned subjects underwent extinction individually in Experiment 1 but with a partner in Experiment 2. In test, both experiments manipulated social buffering (alone vs. accompanied) and context (changed/ABC, unchanged/ACC). Experiment 1 showed more freezing in ABC than in ACC model during the test-alone condition, indicating a fear renewal effect which, however, was absent during the test-accompanied condition. Also, accompanied subjects showed less freezing compared to alone subjects in the ABC model. Experiment 2 showed a similar freezing in ABC and ACC model despite undergoing test alone, implying that social buffering in the extinction disrupted fear renewal. Again, we observed reduced freezing in accompanied relative to alone subjects in the test. The results indicate that social buffering is effective in disrupting fear renewal during context updating.